Diffusion analysis of EFN-MDS structure - Ibrahim, Subariah; Maarof, Mohd. Aizaini (2006)
In general, block ciphers consist of one top-level structural model into which the round function F is plugged into. The study focuses on Extended-Feistel- Network (EFN) that is a generalization of a Feistel Network (FN). This structure is employed in several ciphers that were developed for Advanced Encryption Standard such as CAST-256, MARS and RC6. The problem with EFN is that it requires many rounds when the number of sub-blocks used in EFN is large. This paper proposed a new structural model that can overcome this problem by incorporating EFN with a linear transformation based on Maximum Distance Separable (MDS) codes. The diffusion analysis shows that EFN-MDS requires at most half the number of rounds to achieve completeness property as compared to EFN structure. Therefore the proposed structure is suitable for designing ciphers with scalable